Pentingnya Pendidikan Remaja dan Kesadaran Untuk Mencegah Pernikhan Dini di Pondok Pesantren Al – Hamidy Kebon Talo Desa Labuan Tereng Kecamatan Lembar - Budiman; Husaen Sudrajat; Fatmawati; Muh Asroruddin al-Jumhuri; M. Khairul Izzam; Maelani, Sofhia; Muslihin; Nova Susanto; Heni Handayani; Ainul Istiqomah; Rehanun; Azliza; Nada Nazofa; Siti Rauhun (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2025)
Education is a guide in the growth of children, guiding all of their natural abilities so that they, as human beings and members of society, can achieve the highest possible level of safety and happiness. During adolescence, humans cannot be called adults, but they cannot be called children either. Adolescence is a transitional period from childhood to adulthood, marked by various physical, cognitive, and psychosocial changes. Early marriage is a marriage contract conducted at an age below the legal requirement. Law No. 16 of 2019 amending Law No. 1 of 1974 on marriage states that marriage is only permitted if both the man and woman have reached the age of 19. This socialization activity aims to provide students with an understanding of the importance of education and the negative impacts of marriage conducted under the legal age. This outreach program uses lecture, discussion, and question-and-answer methods. Participants in this socialization program were approximately 50 students from grades IX MTS and XII MA, who gathered in one room to actively participate in the socialization. Based on the results of this socialization session, some students were less active in discussions but still followed the event attentively. Meanwhile, some students actively participated both in discussions and in answering questions from the presenter. The students understood the importance of education, knew the legal age for marriage, and were aware of the negative consequences of marrying underage.